Engineered nanoceria alleviates thermally induced oxidative stress in free-living Breviolum minutum (Symbiodiniaceae, formerly Clade B) - Roger, Liza M.; Russo, Joseph A.; Jinkerson, Robert E.; Giraldo, Juan Pablo; Lewinski, Nastassja A. (Frontiers in Marine Science, 2022)
The breakdown of symbiotic mutualism between cnidarian hosts and dinoflagellate algae partners (i.e. bleaching) has been linked to an immune-like response pathway brought on by a nitro-oxidative burst, a symptom of thermal stress. Stress induced by reactive oxygen/nitrogen species is a problem common to aerobic systems. In this study we tested the antioxidant effects of engineered poly(acrylic acid)-coated cerium dioxide nanoparticles (CeO2, nanoceria) on free-living Symbiodiniaceae (Breviolum minutum), a dinoflagellate alga that forms symbiotic relationships with reef building corals and anemones. Results show that poly(acrylic acid)-coated CeO2 with hydrodynamic diameters of ~4 nm are internalized by B. minutum in under 30 minutes and subsequently localized in the cytosol. Nanoceria exposure does not inhibit cell growth over time, with the exponential growth phase reached between 25 and 30 days of exposure. Aerobic activity and thermal stress when held at 34 °C for 1 hour (+6 °C above control) led to increased intracellular reactive oxygen species (ROS) concentration with time. A clear ROS scavenging effect of the nanoceria was observed with a 5 fold decrease in intracellular ROS levels during thermal stress. The nitric oxide (NO) concentration decreased by ~17% with thermal stress suggesting the rapid involvement of NO scavenging enzymes or proteins within 1 hour of stress onset. The presence of nanoceria did not appear to influence NO concentration. Furthermore, aposymbiotic anemones (Exaiptasia pallida) were successfully infected with nanoceria-loaded B. minutum, demonstrating that inoculation could serve as delivery method. The ability of nanoceria to be taken up by Symbiodiniaceae and reduce ROS production could be leveraged as a potential mitigation strategy to reduce coral bleaching.